2017
DOI: 10.1038/scsandc.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of acute transverse myelitis associated with Staphylococcus aureus bacteremia and osteomyelitis

Abstract: INTRODUCTION: Direct intramedullary infections are considered very rare. Only few reports of Staphylococcus aureus myelitis have been published. CASE PRESENTATION: Our patient, a 79-year-old male, presented with a 2-day history of high-grade fever and high inflammatory markers and progressively developed tetraplegia during hospitalization. Lumbar puncture revealed cerebrospinal fluid pleocytosis and a spinal cord MRI revealed transverse myelitis at the level of C3-C5 and possible osteomyelitis of C5-T1. Two bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
1
5
0
4
Order By: Relevance
“…Because of the potentially grave and poor neurologic outcomes, sharing the experiences of these patients is vital. We suggest that SARS-CoV-2 can produce different multi-systemic involvements via immune-mediated processes that might be the culprit when a patient presents with acute onset of neurological manifestations, especially after microbial infections or vaccinations (Zhao et al 2020 ; Karakonstantis et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the potentially grave and poor neurologic outcomes, sharing the experiences of these patients is vital. We suggest that SARS-CoV-2 can produce different multi-systemic involvements via immune-mediated processes that might be the culprit when a patient presents with acute onset of neurological manifestations, especially after microbial infections or vaccinations (Zhao et al 2020 ; Karakonstantis et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gradualmente el conocimiento de la neuropatología progresó, y una enfermedad tras otra quedó desplazada de esta categoría hasta sólo permanecer la de carácter inflamatorio. (1)(2)(3) La Mielitis transversa aguda es la inflamación aguda de la sustancia gris y blanca en uno o más segmentos medulares adyacentes (habitualmente los torácicos). Las causas incluyen: la esclerosis múltiple, la neuromielitis óptica, las infecciones, la inflamación autoinmunitaria o postinfecciosa, la vasculitis, y ciertos fármacos.…”
Section: Introductionunclassified
“…De manera general, el tratamiento se realiza con medidas sintomáticas y con la corrección de la causa. (1)(2)(3) Por su parte, el síndrome de Froin se define como la presencia de xantocromía, elevación de proteínas e hipercoagulabilidad en LCR como consecuencia de un bloqueo de su circulación secundario a una masa o absceso a nivel medular, o a irritación meníngea, lo que produce la liberación de proteínas (por exudado o trasudado en función de la causa) y la activación de los factores de coagulación. (4) En la RMN se observa como hallazgo característico del bloqueo una hiperintensidad caudal del LCR en T1 y T2.…”
Section: Introductionunclassified
“…Type 2 diabetes, chronic renal failure and ischemic heart disease, about 4 days after the onset of u-like syndrome (with no trauma history) experienced loss of control over both lower limbs, absent sensation from the chest below with constipation and urinary retention. Due to world SARS-CoV-2 (COVID- 19) outbreak, his nasopharyngeal specimen was tested for COVID-19 reverse transcription polymerase chain reaction (RT-PCR) and positive result obtained. Chest x-ray and HRCT suggested severe pulmonary involvement.…”
mentioning
confidence: 99%
“…We only found one study reported a post-infectious acute myelitis as probable COVID-19 complication[6].Because of the potential signi cant morbidity of the disease associated with poor neurologic outcome, experience gained from case reports is important. We believe that SARS-CoV-2 has a potential to produces different extra respiratory multi-systemic involvement as immune-mediated process and complexes, and this should be kept in mind whenever encounter a patient with acute onset of neurological manifestations, especially after microbial infections or vaccinations[6,19].…”
mentioning
confidence: 99%